Intramolecular signal transduction in c-Jun. - Papavassiliou, A G (1995)
The DNA-binding activity of c-Jun is determined by the phosphorylation state of a cluster of threonine and serine residues located near its COOH-terminus. We have analyzed the events that lead to c-Jun activation via dephosphorylation of these sites in response to phorbol esters. Our results indicate that COOH-terminal dephosphorylation is an indirect consequence of a separate phosphorylation event targeted to the NH2-terminus of c-Jun. Thus, the activation of c-Jun DNA-binding potential, caused by COOH-terminal dephosphorylation, may not require the regulation of the kinase/phosphatase system that brings about this change, but rather an alteration in the accessibility of the COOH-terminal phosphoacceptor sites of c-Jun.